2020
DOI: 10.1098/rsos.191422
|View full text |Cite
|
Sign up to set email alerts
|

RGS5 plays a significant role in renal cell carcinoma

Abstract: Recent advances in biotechnology led to generation of large complex biological and clinical datasets that can be used to infer the underlying mechanism of many diseases and arrive at personalized treatments. One of these datasets are the whole genome profiles, including a good collection of publicly available human gene expression datasets. In this project, we analysed gene expression profiles of patients with renal cell carcinoma (RCC). We found that the regulator of G-protein signalling 5 (RGS5) might play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Moreover, RGS5 is a hypoxia-inducible factor-1 dependent involved in the induction of endothelial apoptosis. In our previous study on TCGA data, we found that a high expression level of RGS5 in ccRCC primary tumors is associated with better survival months, and when the grade of ccRCC tumor increases, the RGS5 expression level significantly decreases 29 . Interestingly, cluster ( ) has the highest RGS5 expression level compared to the other clusters, and tumor free patients have a higher level of RGS5 expression than patients with tumor (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, RGS5 is a hypoxia-inducible factor-1 dependent involved in the induction of endothelial apoptosis. In our previous study on TCGA data, we found that a high expression level of RGS5 in ccRCC primary tumors is associated with better survival months, and when the grade of ccRCC tumor increases, the RGS5 expression level significantly decreases 29 . Interestingly, cluster ( ) has the highest RGS5 expression level compared to the other clusters, and tumor free patients have a higher level of RGS5 expression than patients with tumor (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, RGS5 is a hypoxia-inducible factor-1 dependent involved in the induction of endothelial apoptosis 25 . In our previous study on TCGA data, we found that a high expression level of RGS5 in ccRCC primary tumors is associated with better survival months, and when the grade of ccRCC tumor increases, the RGS5 expression level significantly decreases 26 . Interestingly, cluster ( CD 8 < CD 4 ≈ M Φ) has the highest RGS5 expression level compared to the other clusters, and tumor free patients have a higher level of RGS5 expression than patients with tumor (Figure 6A).…”
Section: Resultsmentioning
confidence: 84%
“…Additionally, the landscape of local DNRS for signaling and non-signaling genes is presented in Figure 3H , from which it is seen that a significant increase in the local DNRS of signaling genes occurs in Stage II. When applied to KIRC, it is seen from Figure 3I that the peak of DNRS ( 1.592 04 ) appears in Stage II, after which the lipid levels around the kidney increases rapidly, and then the tumor invades the renal vein ( Su and Shahriyari, 2020 ). As presented in gray in Figure 3I , dynamic changes ( 0.053 ) in the mean gene expression were detected in Stage III and therefore failed to provide timely early-warning signals of the cell fate transition.…”
Section: Resultsmentioning
confidence: 99%